Pre- And Post-Pandemic Determinants of Financial Distress in Property and Real Estate: The Moderating Role of Profitability - Rakhmini Juwita; Iis Solihat; Yeni Widiastuti; Mukhtar Mukhtar; Taufik Akbar (Jurnal Mamangan, 2025)
The research aims to examine the influence of sales growth, leverage, and intellectual capital on financial distress with profitability as a moderating factor before and after the onset of the COVID-19 pandemic. The study focuses on 48 property and real estate sub-sector companies listed on the Indonesian Stock Exchange from 2018 to 2022. Using purposive sampling, 14 eligible companies were chosen for analysis. The data underwent analysis utilizing multiple linear regression, moderated regression analysis, and paired sample t-test methods. Findings indicate that sales growth does not impact financial distress; leverage has a significantly negative effect, while intellectual capital has a notably positive effect. Profitability moderates the influence of sales growth but not leverage or intellectual capital on financial distress. Additionally, it was noted that following the COVID-19 pandemic period, there were decreases in sales growth, intellectual capital, and profitability along with an increase in leverage by 8.75%. The study investigates how sales growth, leverage, and intellectual capital affect financial distress in the property and real estate sector. It goes beyond traditional financial metrics to explore the role of intellectual capital components like human capital, structural capital, and relational capital in mitigating financial distress. The study also examines the effects of the COVID-19 pandemic on the sectors, providing insights into how it has adapted to its challenges.